2019
DOI: 10.1152/ajpheart.00499.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the central and peripheral manifestations of ischemia-induced heart failure in rats

Abstract: Heart failure (HF) is a leading cause of morbidity and mortality for both men and women. Increased sympathetic nerve activity (SNA) is a hallmark of HF and correlates with poor prognosis. We and others have demonstrated that neuroinflammation and renin‐angiotensin system activity are elevated in the cardiovascular‐related regions of the brain in HF, contributing to SNA and the progression of HF. However, most studies that have examined these sympathoexcitatory mediators in the brain in HF have been performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 75 publications
(81 reference statements)
2
14
2
Order By: Relevance
“…As discussed above, this reduction in resting PO 2is is likely attributable to attenuated O 2 delivery. It has been previously shown that female rats express less cardiac dysfunction than males following ischemia-induced infarction (59,69); however, in the present investigation both sexes achieved similar levels of cardiac dysfunction. This key difference may partially explain the greater peripheral dysfunction and lung/body weight ratios found for the female HF group herein, whereas previous studies found fewer effects in females (59,69).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…As discussed above, this reduction in resting PO 2is is likely attributable to attenuated O 2 delivery. It has been previously shown that female rats express less cardiac dysfunction than males following ischemia-induced infarction (59,69); however, in the present investigation both sexes achieved similar levels of cardiac dysfunction. This key difference may partially explain the greater peripheral dysfunction and lung/body weight ratios found for the female HF group herein, whereas previous studies found fewer effects in females (59,69).…”
Section: Discussioncontrasting
confidence: 76%
“…It has been previously shown that female rats express less cardiac dysfunction than males following ischemia-induced infarction (59,69); however, in the present investigation both sexes achieved similar levels of cardiac dysfunction. This key difference may partially explain the greater peripheral dysfunction and lung/body weight ratios found for the female HF group herein, whereas previous studies found fewer effects in females (59,69). However, based on the lack of right ventricle hypertrophy in the present HF animals, the differences in lung/body weight ratio were likely not due to pulmonary congestion and both sexes fall within normal values for both measurements (6,17).…”
Section: Discussioncontrasting
confidence: 76%
“…This structural change was not accompanied by functional injury as the differences seen between prepubertal groups regarding LVEF and FS were insufficient to address systolic dysfunction. The values recorded to Control and Leptin groups are similar to those attributed to normal function by literature 50,51 . In contrast, Marques et al 16 have shown that leptin administration during lactation programmed cardiac structural and functional changes both in young and adult male rats.…”
Section: Discussionsupporting
confidence: 87%
“…All the experimental procedures were approved by the Animal Care and Use . This study was performed in males, as female rats show less hemodynamic and cardiac adjustments and congestive signs after MI than male rats, despite of the same infarct area [21,22].…”
Section: Experimental Modelmentioning
confidence: 99%